Inclusive Higher Education: An Analysis of the Implementation and Effectiveness of the “HEC Policy for Students with Disabilities at Higher Education Institutions in Pakistan 2021” - Manzoor, Afaf; Kamal, Mehwish; Mushtaq, Tehseen (Annals of Human and Social Sciences, 2024)
The Higher Education Commission is also responsible for increasing access and equal opportunities for all students with disabilities. Recently, HEC has launched a policy titled “HEC Policy for Students with Disabilities at Higher Education 2021” which aims to promote inclusive education in all universities and colleges in Pakistan. The study aims to get the opinions of students with disabilities on various components of an inclusive learning environment, from the admission process to the award of a degree. The researchers collected data from 100 students with disabilities enrolled in various programs at universities by using the snowball sampling technique. For this purpose, a survey questionnaire was developed using validation and reliability protocols. The study’s findings revealed that the policy has a positive impact by the higher education institutions under its umbrella. The research will be beneficial for current students, future students, Institutions, and stakeholders.